Caracterización de la Distribución de los Niveles de Presión Sonora para el Casco Central del Cantón de San José - Moya-Bonilla, José Manuel; Monge-Monge, Evandry Alberto (Instituto Tecnológico de Costa Rica, 2015)
Noise is an unwanted and annoying sound that can cause damage to health and environmental problems that affects both rural and urban areas. In recent years, measuring, monitoring and mitigation of noise has become an important issue because of the increase thereof caused by different sources. The objective of this article is to characterize the distribution of sound pressure levels for San José down town. These taking measurements on laboral day in three different lapses, in twelve points of the city using a sound meter 3M SD-2000, besides observations were made to characterize the noise sources. As main results, was observed that average sound pressure levels at the measuring points exceeded the parameters of local legislation from 2dB(A) to 5 dB(A) and that the largest source of noise was caused by traffic.
Proyecto de Graduación (Licenciatura en Ingeniería en Seguridad Laboral e Higiene Ambiental). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2015.
Keywords: Ruido ambiente; Rango horario; Presión sonora; Tráfico; Sonómetro